Field measurements of crack activity and laboratory simulation of crack reflection phenomenon in pavement overlays - Pais, Jorge C. (1998)
This paper shows a field measurement of the crack activity of longitudinal and transversal cracks with a Crack Activity Meter. The Crack Activity Meter was used to measure load associated differential vertical and horizontal movement between the two sides of a crack in pavements before overlay. The crack movements after overlay were calculated with a finite element model. The crack activity before overlay was used to estimate, with a finite element model, the crack activity after overlay function of overlay thickness and material stiffness. The laboratory simulation of reflection cracking was undertaken with the Reflective Cracking Device. The Reflective Cracking Device used with the shear machine introduced by SHRP program, was employed to simulate in laboratory the crack activity patterns measured in the field and the crack activity movements calculated with the finite element model.